Narrative Funktion und christologische Bedeutung der markinischen Erzählung vom Tod Johannes des Täufers (Mk 6:14-29) - Christos Karakolis (Novum Testamentum, 2010)
In the gospel of Mark (6:14-29) the death of John the Baptist is reported in the most detailed fashion, compared to its synoptic parallels. In fact, this is the only extended story in the second gospel that interrupts the gospel’s linear narrative flow by referring to a past event. On the basis of stylistic, structural and narratological observations the present study attempts to illuminate the narrative function and the christological significance of this story by examining the relationship of Mk 6:14-16 to 8:27-29 and 9:9-13, as well as the relationship of 6:17-29 to the Marcan passion narrative. The study concludes that from a narrative, as well as a christological perspective, the second evangelist presents the death of John the Baptist as decisively pointing towards Jesus’ passion.